Assessing the Breeding Potential of Extra‐Long Staple Upland Germplasm in a Cotton Breeding Program. Issue 3 (1st May 2018) - Campbell, B.T.; Hugie, K.L.; Wu, J.; Jones, D.C.
Abstract : Fiber quality improvement of upland cotton ( Gossypium hirsutum L.) is essential to increase the value and competitiveness of cotton fiber. The closely related allotetraploid species G. barbadense L. has long been targeted as a source of beneficial fiber quality alleles. Although interspecific hybridization between G. hirsutum and G. barbadense results in fertile offspring, cultivar development programs have seen little success using this approach. In this study, we evaluated the breeding potential of extra‐long staple (ELS) upland accessions that presumably contain G. barbadense introgressions. As expected, ELS upland accessions produced long fibers with overall excellent mean fiber quality performance. Genetic effects indicated that ELS upland accessions transmitted both additive and nonadditive beneficial alleles for fiber length and micronaire. However, ELS upland accessions also transmitted negative effects for lint percentage, lint yield, and fiber strength. Results suggest that ELS upland accessions are a good source for improving fiber length but also support the idea that linkage drag and skewed chromatin transmission, often seen in progeny derived from interspecific hybridization, may still proliferate in offspring derived from ELS upland accessions.